Vocabulary Language and Discourse Competence as a Model for Semantic Course Syllabus in Indonesian Language and Literature Education Study Program - Sintowati Rini Utami; Eriyani, Reni Nur (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2022)
This study will develop a syllabus model for the Indonesian Semantics course in the Indonesian Language and Literature Education Study Program. This research is part of research on the syllabus model for the Indonesian Semantics course in the Indonesian Language and Literature Education Study Program. Preliminary research, analyzing the syllabus of Sematic courses from several universities that teach the same study. The description of the study material for the Semantics course is based on a descriptive analysis with a content analysis study of the various contents of the study material in the Indonesian semantic syllabus in several Indonesian Language and Literature Education Study Programs. The results of this content analysis describe the study material for the scope of the Semantics course in the syllabus, namely the general concept of meaning (38%) and the definition of meaning (37%); types of lexical meaning (62%), the concept of relation meaning synonyms, antonyms, hyponyms (40%); the concept of the meaning component (14%); the concept of the meaning field (67%); the concept of changing meaning (50%), implicit semantic and syntactic compatibility (50%), semantic and pragmatic compatibility are not explicitly studied (100%); based on Semantic study materials as linguistic vocabulary that are less espouse towards diction mastery and vocabulary teaching are predicted to show less espouse for the formation of discourse competence (30%). Discourse competence is the pedagogic goal of semantic concept study materials as linguistic vocabulary. Abstrak Penelitian ini akan mengembangkan model silabus mata kuliah Semantik Bahasa Indonesia di Prodi Pendididkan Bahasa dan Sastra Indonesia. Penelitian ini sebagai bagian rangkaian penelitian model silabus mata kuliah Semantik Bahasa Indonesia di Prodi Pendididkan Bahasa dan Sastra Indonesia. Penelitian awal, menganalisis silabus mata kuliah Semantik dari beberapa perguruan tinggi yang mengajarkan kajian yang sama. Deskripsi bahan kajian mata kuliah Semantik didasarkan pada analisis deskriptif dengan kajian content analysis terhadap berbagai isi bahan kajian dalam silabus semantik bahasa Indonesia yang ada di beberapa Prodi Pendidikan Bahasa dan Sastra Indonesia. Fokus dan objek penelitian berkenaan dengan aspek kebahasaaan kosakata berdasarkan kajian semantik. Hasil analisis isi ini mendeskripsikan bahan kajian ruang lingkup mata kuliah Semantik dalam silabus adalah konsep umum makna (38%) dan definisi makna (37%); jenis makna leksikal (62%), konsep relasi makna sinonim, antonim, hiponim (40%); konsep komponen makna (14%); konsep medan makna (67%); konsep perubahan makna (50%), kesesuaian semantik dan sintaksis secara implisit (50%), kesesuaian semantik dan pragmatik tidak dijadikan bahan kajian secara eksplisit (100%); berdasarkan bahan kajian semantic sebagai kebahasaan kosakata yang kurang mendukung ke arah penguasaan diksi dan pengajaran kosakata diprediksi menunjukkan kurang mendukung pembentukan kemahirwacanaan (30%). Kemahirwacanaan adalah tujuan pedagogik dari bahan kajian konsep semantik sebagai kebahasaan kosakata.